Work-related allergy in medical doctors: atopy, exposure to domestic animals, eczema induced by common chemicals and membership of the surgical profession as potential risk factors - Kanayama, Hitomi (Springer-Verlag, 2011)
PURPOSE: To investigate the risk factors associated with work-related allergy-like symptoms in medical doctors. METHODS: Self-administered questionnaire survey and CAP test were conducted among medical school students in the 4th grade of their 6-year medical course in 1993–1996 and 1999–2001. Follow-up questionnaires were sent in 2004 to the graduates. These questionnaires enquired into personal and family history of allergic diseases, lifestyle, history of allergy-like symptoms including work-relatedness and occupational history as medical doctors. Relationships between allergy-like symptoms and relevant factors were evaluated by multivariate logistic regression analysis. RESULTS: Of 261 respondents at the follow-up survey, 139 (53.3%) and 54 (20.7%) had a history of any allergy-like symptoms and any work-related allergy-like symptoms, respectively. Female gender and family history of allergic diseases were significantly associated with any allergy-like symptoms. Personal history of allergic disease, exposure to domestic animals, eczema caused by rubber gloves, metallic accessories, or cosmetics during schooling days, and membership of the surgical profession were significant risk factors for work-related allergy-like symptoms. On the contrary, to work-related allergy-like symptoms, gender, age, and smoking status were not significantly related, and consumption of prepared foods was inversely related. CONCLUSIONS: Personal history of atopy and eczema induced by common goods and the history of keeping domestic animals may be predictors of work-related allergy-like symptoms in doctors. After graduation from medical school, physicians start with exposure to various allergens and irritants at work, which relate to work-related allergy-like symptoms, especially for surgeons. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00420-011-0682-z) contains supplementary material, which is available to authorized users.